Chinese Cultural Revolution In 1966-1976 - Fajar Harianto; Sumardi Sumardi; Sugiyanto Sugiyanto (History Education, University of Jember, 2018)
The Cultural Revolution is a great campaign that made China suffered paralysis in 1966-1976 led by Mao. The Cultural Revolution because there are two factors, the first is the decline of public trust in Mao for policy failures leap far ahead so that Mao stepped down from government. Secondly, Mao wanted to restore China to communism, because China has been influenced by the understanding of the capitalist and liberal. The Cultural Revolution has failed and resulted in many victims, especially the peasants and workers. These conditions cause this interesting study to be carried out, because of the Cultural Revolution can paralyze China in 1966-1976. The problems of this study are; (1) how the background of the onset of the Cultural Revolution; (2) how the Cultural Revolution took place; (3) the influence of the Cultural Revolution to the Chinese community. The purpose of this study is; (1) to analyze the background of the Cultural Revolution; (2) to analyze the process of the Cultural Revolution; (3) to analyze the influence of the Cultural Revolution to the Chinese community. The method used is the method of historical study, historical method is the process of testing and critically analyze the records and relics of the past. The conclusion of this study that used Mao's Cultural Revolution to restore public confidence by doing defamation to his enemies to again be the leader. The results of the Cultural Revolution is a great famine, causing many casualties. Keywords :Revolution, Culture, Cina